2006
DOI: 10.1182/blood-2005-06-2318
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of intrinsic, extrinsic, and endoplasmic reticulum-mediated apoptosis by imatinib mesylate combined with arsenic trioxide in chronic myeloid leukemia

Abstract: A treatment strategy that combines arsenic trioxide (ATO) with the tyrosine kinase inhibitor imatinib mesylate (STI571, Gleevec) appears to induce markedly more cell apoptosis than imatinib mesylate alone in chronic myeloid leukemia (CML). To understand the mechanisms underlying the synergistic/additive action of these agents, we applied cDNA microarrays, component plane presentation integrated self-organizing map (CPP-SOM), and methods of protein biochemistry to study cell apoptosis induced by imatinib mesyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
64
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(70 citation statements)
references
References 39 publications
(40 reference statements)
6
64
0
Order By: Relevance
“…Some studies also suggested that ER stress could be involved in the anticancer action of arsenic trioxide (Du et al. 2006; Chen et al. 2012; Chiu et al.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies also suggested that ER stress could be involved in the anticancer action of arsenic trioxide (Du et al. 2006; Chen et al. 2012; Chiu et al.…”
Section: Introductionmentioning
confidence: 99%
“…ATO is used to be a therapeutic agent for acute promyelocytic leukemia (16). ATO also provokes ER stress that leads to downregulation of calcium signaling resulting in apoptosis (17). SP600125 is widely known as a reversible ATP competitive inhibitor of c-Jun N-terminal kinase (JNK).…”
Section: Nupr1 Is Induced By Various Stress Agentsmentioning
confidence: 99%
“…Real-time RT-PCR analysis of BCR/ABL transcripts was performed as previously described (5,7). All experiments were performed 4 times, and the 2-sided paired t test was used for statistical analysis.…”
Section: Real-time Rt-pcrmentioning
confidence: 99%
“…Arsenic compounds such as arsenic trioxide (As 2 O 3 ) and arsenic sulfide (As 4 S 4 , AS) have been used in the treatment of CML before the era of modern chemotherapy and more recently have been shown to be effective, particularly in combination with all-trans retinoic acid, in the treatment of acute promyelocytic leukemia (APL) (4). Indeed, some previous studies have reported the potentiating effects of As 2 O 3 when used in combination with IM in CML cells (5,6). A combination of AS and IM also induced apoptosis in CML cells (7) and the fact that AS can be used orally in humans as a relatively safe agent (8) makes it potentially a more appropriate partner for IM in anti-CML therapy.…”
mentioning
confidence: 99%